Pedagogical Content Knowledge in Chemistry Education: Its Significance for Pre-Service Chemistry Teachers - M, Munawwarah; Cahyani, Vika Puji (Journal of Tropical Chemistry Research and Education, 2025)
This study examines the significance of Pedagogical Content Knowledge (PCK) in chemistry education, specifically its role in pre-service chemistry teacher training. Through a comprehensive review of 14 articles, the research identifies key themes related to the development, application, and impact of PCK on chemistry teaching practices. The majority of the articles emphasize the importance of integrating PCK into teacher training programs, highlighting the effectiveness of practice-based and constructivist learning approaches to bridge the gap between content knowledge and teaching strategies. PCK was found to influence teaching methodologies, allowing teachers to tailor their approaches to specific chemistry topics and manage classroom dynamics effectively. However, the study also reveals significant gaps in the application of PCK in classroom management and assessment practices, areas that require further exploration. The findings suggest that although PCK plays a critical role in improving teaching quality, its integration into classroom management and assessment is still underexplored. The research recommends future studies to focus on these areas, particularly in secondary and higher education settings, to refine the application of PCK across various aspects of chemistry teaching. This research contributes to a deeper understanding of PCK's role in teacher preparation and offers directions for future research to enhance the development of pre-service chemistry teachers and improve overall teaching effectiveness.